PENGEMBANGAN MEDIA PEMBELAJARAN SISTEM PENCERNAAN MAKANAN DISERTAI VIRTUAL LABORATORYDI SMP - Purwanti, Titis; Habibah, Noor Aini; Supriyanto, Supriyanto (Journal of Biology Education, 2014)
The purpose of this research is developing and knowing assess the feasibility of learning media digestive of food system with virtual laboratory in Junior High School. The research was conducted at Departement of Biology Semarang State University and Junior High School 13 Magelang with research design and development (Research and Development /R&D). The Product usage test samples taken by convenience sampling method. Assessment results matter experts and instructional media specialist showed a digestive system media with a virtual laboratory is very fit for use as a media of learning. Teachers responded that the media is very supportive to learning activities of biology. Students in product testing and product usage testing responded very well to the criteria for the use of instructional digestive system media accompanied virtual laboratory. The trial results showed a classical learning outcomes students achieve 86.60%Â  KKM â¥75. Based on the results of the research study media of digestive system accompanied virtual laboratory fit for use as a media of learning biology in Junior High School.Tujuanpenelitianiniadalahmengembangkandanmengetahuikelayakan media pembelajaransistempencernaanmakanandisertaivirtual laboratory di SMP. Penelitiandilaksanakan di JurusanBiologiUniversitasNegeri Semarang dan SMP Negeri 13 MagelangdenganrancanganPenelitiandanPengembangan (Research and Development/R&D). Sampelujicobapemakaianprodukdiambildenganmetodeconvenience sampling. Hasilpenilaianahlimateridanahli media menunjukkan media pembelajaransistempencernaanmakanandisertaivirtual laboratory di SMP layakdigunakansebagai media pembelajaran. Guru menanggapibahwa media tersebutsangatmendukunguntukkegiatanpembelajaranbiologi. Tanggapan siswaterhadappenggunaan media pembelajaransistempencernaanmakanandisertaivirtual laboratory.padaujicobaprodukmaupunujicobapemakaianproduksangatbaikHasilbelajarsiswa secaraklasikalsebesar 86,60% Â dengan KKM 75.. Berdasarkanhasilpenelitiandisimpulkan bahwa media pembelajaransistempencernaanmakanandisertaivirtual laboratorylayakdigunakansebagai media pembelajaranbiologi di SMP.